W poszukiwaniu języka. O retoryce Partii Kobiet - Sobczak, Barbara (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
To make the political presence of women more visible in modern public discourse it is necessary to work out a language that would represent them appropriately. An analysis of the rhetoric of the Women’s Party (Polish: Partia Kobiet), established in 2007, shows how this problem is handled by the officials of the party. The starting point for the discussion is the thesis that rhetoric discourse is initiated and shaped by a given rhetoric situation (as understood by L.F. Bitzer). In the analysed instance, it is determined by: 1) social and political circumstances surrounding the emergence of the party, no deep-rooted feminist tradition in particular; negativism in the approach towards women’s movements in general reflecting senses and moods dominating within society, marginalisation of women’s issues and women’s voices in mainstream political discourse, 2) historical conditioning and culturally dominant position of the male model of discourse in public address, 3) the attempt to get involved in the discourse as wide audience as possible, coupled with the belief that the sense of unity is to be based on the gender identity. The analysis of the texts available on the web page of the party, viewed as being fully of representative nature for the party, shows that the rhetoric of the Women’s Party is not heterogeneous. It oscillates between the rhetoric of co-operation (through the agency of which the party looks for tools instrumental for achieving some kind of agreement and dialogue in the public debate) and the rhetoric of hatred, already well-established in Polish political discourse (which undermines the formerly mentioned conciliatory attitude in dialogue and co-operation). As a result, a type of a communication ensues that is not free from paradoxes and one that makes a creation of a coherent and consistent message impossible, and therefore hinders a creation of a credible image of the party.